ХАЛЫҚ ТЕРМЕ–ТОЛҒАЎ ЖЫРЛАРЫНЫҢ ЖАСЛАР ТӘЛИМ-ТӘРБИЯСЫНДА ТУТҚАН ОРНЫ - Ережепов, А.А. (SCIENCE and SOCIETY, 2019)
The article deals with the data about the art of jirau of Karakalpaks the analysis of features and interpretation of certain songs, coronach that have the character of spiritual-moral upbringing of students, based on the national mentality and anthropological, ethnic, cultural-enlightening approaches related to ethnopedagogical features.
Keywords: skills of jiraw of Karakalpaks; customs and traditions; national upbringing; moral; spirituality; singing-coronach and throaty singing